La decorazione della grotta degli Animali: note sulle vicende conservative dall’epoca sabauda ad oggi - Mozzo, Marco (Opus Incertum, 2019)
The essay deals with events concerning the history of the conservation of the “Cave of the Animals” from the Savoy period to the present day. Thanks to documentation found in the Central State Archive, it was possible to analyse some aspects of its maintenance and the proposals concerning the main restorations made to the sculptures in the Garden: the fountain of Hercules and Antaeus, as well as to the Cave of the Animals. This maintenance continued sporadically over the years until the Eighties of the last century, when important restoration activities were undertaken. This allowed the progressive recovery of the decorated surfaces and of the hydraulic system of the Cave of the Animals.